Description of a new and critically endangered species of Atheris (Serpentes: Viperidae) from the Southern Highlands of Tanzania, with an overview of the country’s tree viper fauna - Menegon, Michele; Davenport, Tim R. B.; Howell, Kim M. (Zootaxa, 2011)
A new species of arboreal forest viper (Serpentes: Viperidae: Atheris) from a forest fragment in the Southern Highlands of Tanzania is described and named Atheris matildae sp. nov. The species resembles the forest horned viper, Atheris ceratophora Werner, by bearing horn-like supraciliary scales but it differs in size, body proportions, scalation, scale ultrastructure, and distribution. Genetic divergence is also assessed and the two species have an estimated divergence time of approximately 2.2 million years. An overview of the genus Atheris in Tanzania, including new distribution data, is presented and the conservation status of the new taxon is discussed.